ISLAM AND THE ASEAN ECONOMIC COMMUNITY (AEC): A PERSPECTIVE OF ISLAMIC ECONOMY IN BUILDING A MULTICULTURAL SOCIETY IN INDONESIA - Supriono, Supriono - (ADDIN, 2016)
Problems faced by society in general now is the emergence of a view that places the material aspect which is free of the dimension value in the dominant position. View of life that is based on the ideology of materialism which then push human behavior into economic principals hedonistic, materialistic and secularistic. Indonesia as the country with the world’s largest Islamic community, as well as the role of Muslims in a bid for independence is one proof that Islam teaches morality and responsibility in defending the homeland. Economic role is as the main street permanence in the life of the state. Infact, Islam teaches its followers to be a lot of the individuals who are experts in economic development as a means contributive to realize the vision of building a multicultural Indonesia.